High Visceral Adipose Tissue Density Correlates With Unfavorable Outcomes in Patients With Intermediate-Stage Hepatocellular Carcinoma Undergoing Transarterial Chemoembolization - Li, Qiang; Zhang, Lei; Hou, Zhong-Heng; Zhao, Dong-Xu; Li, Jian-Bin; Zhang, Shuai; Yin, Yu; Ni, Cai-Fang; Chen, Tao (Frontiers in Cell and Developmental Biology, 2021)
Objectives: This study aimed to evaluate the association between different body composition features with prognostic outcomes of intermediate stage hepatocellular carcinoma (HCC) patients treated with transarterial chemoembolization (TACE). Methods: The areas and density of skeletal muscle area (SM) and adipose tissue [subcutaneous (SAT); visceral (VAT)] were calculated on the pre-TACE CT scans. Overall survival (OS) and progression-free survival (PFS) curves were calculated using the Kaplan–Meier method and compared with log-rank test. The discrimination and performance of body composition features were measured by area under time-dependent receiver operating characteristic (ROC) curve. Univariate and multivariate Cox proportional hazard analyses were applied to identify the association between body composition parameters and outcomes. Results: A significant prolonged OS and PFS was displayed by Kaplan–Meier curve analysis for HCC patients with VAT HU below −89.1 (25.1 months, 95% CI: 18.1–32.1 vs. 17.6 months, 95% CI: 16.3–18.8, p < 0.0001, 15.4 months, 95% CI: 10.6–20.2 vs. 6.6 months, 95% CI: 4.9–8.3, p < 0.0001, respectively). The 1-, 2-, 3-, and 5-year OS area under the curve (AUC) values of the VAT HU were higher than the other body composition parameters. Meanwhile, it is also found that 3-, 6-, 9-, and 12-month PFS AUC values of VAT HU were the highest among all the parameters. Univariate and multivariate Cox-regression analysis suggested a significant association between VAT density and outcomes (OS, HR: 1.015, 95% CI: 1.004–1.025, p = 0.005, PFS, HR: 1.026, 95% CI: 1.016–1.036, p < 0.0001, respectively). Conclusion: The VAT density could provide prognostic prediction value and may be helpful to stratify the intermediate stage HCC patients.